Advancing the prevention and treatment of HIV in children: priorities for research and development. Issue 9 (September 2022) - Penazzato, Martina; Townsend, Claire L; Sam-Agudu, Nadia A; Ruel, Theodore D; Archary, Moherndran; Bekker, Adrie; Cressey, Tim R; Colbers, Angela; Sugandhi, Nandita; Rojo, Pablo; Rakhmanina, Natella; Watkins, Melynda; et al.
Summary: Safe and effective paediatric formulations of the most promising antiretroviral drugs are crucial to advance the treatment and prevention of HIV in neonates, infants, children, and adolescents. The WHO Paediatric Drug Optimization for HIV (PADO-HIV) group brings together stakeholders and experts every 2–3 years to identify priority products and define research gaps in the development of new HIV drugs and formulations for children in low-income and middle-income countries. PADO-HIV 5 met from Sept 27 to Oct 15, 2021. The group evaluated HIV agents from known and novel drug classes, oral and parenteral long-acting formulations, and developments in broadly neutralising antibodies, and included focused sessions on neonates and new delivery technologies. A list of medium-term and long-term priorities was generated, and research questions were defined. This forward-looking analysis is intended to provide guidance to funders, drug developers, and researchers, and to accelerate access for children to the best HIV drugs and formulations.